The throne of fire - Riordan, Rick. (New York : Hyperion Books, 2011)
Carter and Sadie, offspring of the brilliant Egyptologist Dr. Julius Kane, embark on a worldwide search for the Book of Ra, but the House of Life and the gods of chaos are determined to stop them.
Angela Misa
Keywords: Large type books; Adventure and adventurers -- Fiction; Voyages and travels -- Fiction; Egyptian mythology -- Fiction; Magic -- Fiction; Siblings -- Fiction; Large type books